The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/2191-0855-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a novel Pichia pastoris strain for production of xanthophylls

Abstract: In this study, we used the yeast carotenogenic producer Pichia pastoris Pp-EBIL strain, which has been metabolically engineered, by heterologously expressing β-carotene-pathway enzymes to produce β-carotene, as a vessel for recombinant astaxanthin expression. For this purpose, we designed new P. pastoris recombinant-strains harboring astaxanthin-encoding genes from carotenogenic microorganism, and thus capable of producing xanthophyllic compounds. We designed and constructed a plasmid (pGAPZA-WZ) containing bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 36 publications
(51 reference statements)
0
21
0
1
Order By: Relevance
“…Thus, these engineered hosts are competitive to natural microbial β-carotene producers currently used for production at industrial scale such as the microalga Dunaliella salina which has been reported to synthesize 37.3 mg g −1 DCW per day (García-González et al 2005) or the fungus Blakeslea trispora which could be optimized to produce up to 55 mg g −1 DCW of β-carotene per day (Roukas et al 2015). In contrast, yields of other hosts such as C. glutamicum or P. pastoris are relatively low in the μg g −1 DCW to single-digit mg g −1 DCW range (Araya-Garay et al 2012; Henke et al 2016).…”
Section: Microbial Production Of Different Terpenoid Classesmentioning
confidence: 99%
“…Thus, these engineered hosts are competitive to natural microbial β-carotene producers currently used for production at industrial scale such as the microalga Dunaliella salina which has been reported to synthesize 37.3 mg g −1 DCW per day (García-González et al 2005) or the fungus Blakeslea trispora which could be optimized to produce up to 55 mg g −1 DCW of β-carotene per day (Roukas et al 2015). In contrast, yields of other hosts such as C. glutamicum or P. pastoris are relatively low in the μg g −1 DCW to single-digit mg g −1 DCW range (Araya-Garay et al 2012; Henke et al 2016).…”
Section: Microbial Production Of Different Terpenoid Classesmentioning
confidence: 99%
“…Araya‐Garay et al. constructed β‐carotene‐producing Pichia strain Pp‐EBIL as described above and used it as a platform strain for further metabolic engineering modifications . Two genes, crtW and crtZ , from Agrobacterium aurantiacum were cloned under the GAP promoter to generate the plasmid pGAPZA‐WZ.…”
Section: Metabolic Engineering Of P Pastorismentioning
confidence: 99%
“…The methylotrophic yeast Pichia pastoris (renamed Komagataella phaffii 9 ) is currently used industrially for production of recombinant proteins 10 . Recently, P. pastoris has also been used for production of metabolites including astaxanthin and isobutanol from sugar 11 , 12 . However, relative to model organisms, most native methylotrophs lack the genetic tools and depth of characterisation necessary for the successful metabolic engineering of high-yield and heterologous pathways.…”
Section: Introductionmentioning
confidence: 99%